DFT Investigation on the Electronic Properties and Intramolecular Hydrogen Bond of Trans-Cis and Cis-Trans Methyl Substituted N-Benzoyl-N’-(2-pyridyl)thiourea. - Draman, Rafie; Mohd Yusof, Mohd Sukeri; Abdul Kadir, Maisara (Journal of Science and Technology, 2020)
Five single molecule methyl substituted Benzoyl pyridinylthiourea compounds namely N-benzoyl-N’-(2-pyridyl)thiourea, N-benzoyl-N’-(6-methyl-2-pyridyl)thiourea, N-benzoyl-N’-(5-methyl-2-pyridyl)thiourea, N-benzoyl-N’-(4-methyl-2-pyridyl) thiourea and N-benzoyl-N’-(3-methyl-2-pyridyl)thiourea are investigate theoretically for trans-cis and cis-trans conformation at B3LYP 6-31G(d,p) level of theory. Electronic properties have been analyzed by Gaussian 09W package and AIMAll code. Methyl substituent and its position give noticeable effect to reactivity, stabilization, and hydrogen bond interaction strength. AIM prove that 6-methyl substituted on pyridyl ring has significant effect to preferent conformation.